Sonographic evaluation of a thrombus in the jugular vein of an equine - Belotta, Alexandra Frey [UNESP]; Santos, Debora Rodrigues dos [UNESP]; Zardo, Karen Maciel [UNESP]; Babicsak, Viviam Rocco [UNESP]; Oliveira, Hugo Salvador [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP]; Vulcano, Luiz Carlos [UNESP]; Dantas, Gabriela Nascimento [UNESP]; Chiacchio, Simone Biagio [UNESP] (Univ Federal Rural Pernambuco, 2011)
An equine, American Troter, female, 5 years of age, was referred to the Diagnostic Imaging Sector at the Veterinary Hospital of the FMVZ, Unesp, Botucatu Campus, with suspected jugular thrombosis. Ultrasonographic findings were heterogeneous tissue at the lumen of the right jugular vein with blockage of its diameter and collateral blood flow formation.
Keywords: equine; thrombosis; ultrasound